p1 + (p2 - p1) * t = q1 p2 + (p3 - p2) * t = q2 p3 + (p4 - p3) * t = q3 q1 + (q2 - q1) * t = r1 q2 + (q3 - q2) * t = r2 p(x) = r1 + (r2 - r1) * t

p(y) =

r1 + (r2 - r1) * t

Where

0 < t < 1 : Step of 0.1

p1 = position of point number 1, in this case 9

p2 = position of point number 2, in this case 11

Here I derived all of q1, q2, q3. (Total # of points for each q is 11. Therefore there is 33 points.)

Then i derived all of r1 & r2 (Total # of points for each r is 11. Therefore there is 22 points.

and then p(x), p(y) (Total # of points for each r is 11. Therefore there is 11 points.